PENYULUHAN PENINGKATAN PENGETAHUAN CARA MENJAGA KESEHATAN GIGI PADA SISWA SEKOLAH DASAR - Mulyati, Susi; Hutapea, John Hendrik Sahat M; Mahanani, Dian; Puspita, Irma Yudith Ayu; Rustamadji, Ratna Sekundaria; Kurniawan, Yang Fajar; Putri, Zahra Tania; Priadi, Putri Zahra; Pratiwi, Diana Adi; Destyanti, Annisa A (LPPM Universitas Flores, 2025)
Oral and dental health issues are critical in public health development, particularly among elementary school-aged children. Early dental care prevents enamel damage and supports the strength of children’s developing teeth. Children have a set of evenly aligned teeth at a young age that grow and develop gradually. Introducing oral hygiene habits early is essential. Failure to prevent cavities in school-aged children can hinder their long-term growth if specific measures are not taken, such as addressing dietary habits like consuming chicken and other foods. Such issues may disrupt a child’s developmental process. This community service initiative aimed to educate elementary school children to enhance their oral and dental health knowledge. The activity was conducted on Friday, December 13, 2024, at SDN (Elementary School) Kuningan Barat 01, South Jakarta. The program involved direct educational counselling sessions with 118 participants. Evaluation was performed through questionnaires to measure knowledge levels, assessed via pre-test and post-test results. The findings revealed a significant improvement in the children’s understanding of oral and dental health, evidenced by the post-test results, in which 80 respondents (67.78%) achieved high scores.